PSYCHOLOGICAL AND DIDACTICAL CONDITIONS OF IMPROVEMENT IN LEARNING HIEROGLIPHIC WRITING EFFICIENCY (AT THE EXAMPLE OF JAPANESE) - Naumova, Julia (PSYCHOLOGICAL JOURNAL, 2019)
The article is devoted to the substantiation and description of the results of introducing the multipronged methodology of improving the efficiency of learning hieroglyphic writing into the educational process of training the students of the departments of oriental languages. ​​ Hieroglyphic writing differs significantly from the European way of language codification of reality. Theoretical analysis of the study of this issue and the empirical experience obtained directly in our study prove that the use of standardized programs while learning the hieroglyphics, as well as of the methods used by the Japanese themselves, do not give the desired effect. Students demonstrate poor performance when learning hieroglyphics particularly and often lose their motivation to learn the language overall. Methodologists who seek techniques and methods to improve the efficiency of mastering Eastern languages ​​by European speakers point out the need to take into account the etymological, cultural basis of the hieroglyphic writing system, believing that it is necessary for students to familiarize themselves with the character and philosophy of the Chinese and Japanese visualization of the Universe and the psychological components of a learning process. At the same time, special scientifically based programs that take into account the full range of psychological characteristics of mastering the hieroglyphic languages ​​ actually do not exist in Ukraine. Out of the psychological components, linguists pay attention mainly to the processes of memorization and / or motivation. The purpose of this article is to describe, substantiate and bring the evidence base of the effectiveness of introducing into the educational process a program that optimizes the success of students about learning hieroglyphics, taking into account the implementation of certain psychological and pedagogicalconditions. In our methodology conditions are defined as follows: the inextricable link between the language and the culture and history of ancient China and Japan; students’ assessment and accounting of their own cognitive styles of learning and solving educational tasks; reliance on the students` world of images e, management and self-management of the process of assimilation of visual-semantic images of hieroglyphic signs; purposeful development and expansion of the repertoire of students` learning strategies while mastering hieroglyphics; management and support of students` motivation, helping them with formulating goals, objectives and finding their own resources to achieve them; implementation of an individual-personal approach, implying the distribution of responsibility for the results of educational activities between the teacher and the student; introduction of a transparent system of assessment and control in accordance with the selected hieroglyphic competencies, for which the forms of control, criteria, content and deadlines for the implementation of training tasks must be presented to the student in advance. Thanks to the creation of the described conditions, it becomes possible for students to set a goal, develop a plan, select the necessary strategies to achieve results. The implementation of these conditions is determined by the principles of cognitive, competence-based and strategic approaches to the training and professional training of students. In particular, the cognitive approach to the study of hieroglyphics focuses attention on the students’ awareness of the psycholinguistic patterns of language learning, provides students with an understanding of the process of learning a new one, taking into account the current level of competencies and their improvement. This approach, based on psychological and didactic teaching methods, creates the basis for the formation of the necessary level of foreign language competencies, in particular, hieroglyphic ones. When Students master the learning strategies it allows them to expand their individual cognitive potential, to intensify and optimize the process of mastering the language, to learn how to adequately use their own strategic resources, taking into account the specifics of language learning. The implementation of the program, taking into account the above-mentioned psychological and pedagogical conditions, made it possible to identify and statistically prove its effectiveness. Students who have completed an elective program have demonstrated certain progress about mastering the hieroglyphic competencies. In particular, significant improvements have been noted about mastering such types of hieroglyphic competencies as strategic and linguistic ones. Comparison of the shares of positive shifts after the experiment in the experimental and control groups using the Fisher’s angle transformation method φ * showed improvement about the level of mastering the general hieroglyphic competence at the significance level (p ≤ 0.01) in the group of students who completed the program.